Increased hatching success as a direct benefit of polyandry in birds. (1st January 2015) - Reding, Luke
Abstract: Multiple mating by females is difficult to explain in primarily socially monogamous taxa such as birds because mating outside the pair bond often provides no obvious benefit to females. Although indirect selection is often invoked to explain the evolution of polyandry, current evidence suggests that selection on indirect benefits of mating is weak. Here, I consider a direct benefit of remating in birds: increased fertilization success. I test whether increased hatching success of a female's eggs is related to rates of extra‐pair paternity (EPP), a proxy of polyandry, across 113 bird species. I use two statistical approaches, control for phylogenetic uncertainty, and assess the fit of competing evolutionary models. Results show there is indeed a positive relationship between rates of EPP and hatching success in birds. I propose that by mating with many males, females may increase their fertility. I end by discussing the biological rationale for this explanation, alternative interpretations of the results, and how this study furthers our understanding of polyandry and mating system evolution.